The Effect of Cooperatif Learning Type Snowball Throwing Model Containing Science Literacy on Students’ Learning Competencies in Human Excretory System Material - Cheni Wulandari; Relsas Yogica; Indra Hartanto; S. Syamsurizal (Universitas Negeri Padang, 2019)
This research is based on the problems that exist in Batusangkar 1 Junior High School, namely the learning model that is less varied, student learning abilities are still low, teacher-centered learning. The effort that can be done is to apply the snowball throwing learning model with scientific literacy in the material of Excretion System at Batusangkar 1 Junior High School. The purpose of this study was to determine the effect of the application of the snowball throwing learning model containing scientific literacy on the learning competencies of class VIII students of Batusangkar 1 Junior High School. This study was an experimental study with a randomized posttest control group design. The study population was grade VIII students of SMPN 1Batusangkar in the academic year 2018/2019 which spread to nine classes. The research sample was taken using cluster random sampling. The results were selected class VIII.3 as the experimental class and class VIII.4 as the control class. The hypothesis in this study was tested using the t-test. The results of the study using the t-test can be concluded that the competency of student knowledge about the value of tcount 4.31> ttable 1.67, in the attitude of competency the tcount 5.41> ttable 1.67, and competency skills tcount 3.85> ttable 1.67. This shows that the hypothesis is accepted. So, it can be concluded that the application of the snowball throwing model with scientific literacy can improve the competency of knowledge, attitudes, and skills of class VIII Batusangkar 1 Junior High School.